New Developments in Goal Setting and Task Performance - Locke, Edwin A., editor 308516; Latham, Gary P., editor 433139 (New York : Routledge, 2013)
This book concentrates on the last twenty years of research in the area of goal setting and performance at work. The editors and contributors believe goals affect action, and this volume has a lineup of international contributors who look at the recent theories and implications in this area for IO psychologists and human resource management academics and graduate students.